Discounting in developing countries : experimental evidence from Timor-Leste - Botelho, Anabela (2006)
We conduct laboratory experiments in Timor-Leste designed to test if individual discount rates vary with the time horizon for which the rate is elicited. Our experiments test a design that has been successfully employed in field experiments in developed countries, and that avoids several confounds of previous procedures. We find that there is considerable heterogeneity in individual discount rates, and that this heterogeneity is associated with observable demographic characteristics. We also find evidence that is consistent with exponential discounting behavior, although our sample sizes do not allow us to definitively reject alternative specifications. We discuss modifications of our laboratory experiments that would facilitate field experiments in Timor-Leste.